PERANCANGAN SISTEM INFORMASI PEMBUATAN SURAT KELUAR BERBASIS VB .NET DAN MS. ACCESS DI KANTOR DESA KARYASARI - Siti Nurazizah Sulaemani Azizah (INFOKOM (Informatika & Komputer), 2022)
Technological developments in 2022 are increasing rapidly in various institutions and the wider community, this can improve the performance of employees in terms of time and efficiency, especially in the use of a computer device. At the Karyasari village office, Rengasdengklok district, Karawang district, who is in charge of making outgoing letters, already using a computerized system, but it is still done by typing manually so that it often experiences errors in inputting words and inefficient processing time. In addition, the management of outgoing mail reports is also less than optimal. From the occurrence of these errors lead to wastage. Therefore, from all these problems, a Visual Basic .NET and Microsoft Access-based system will be designed that will facilitate employees in making outgoing letters and a system that can manage citizen’s data properly. The research method that will be used is the Waterfall method in order to make the system simple and work sequentially, so that the system can be well organized. With the application for making outgoing letters, it is hoped that it can help reduce the existing risks